Sistem Informasi Repository Berbasis Web Pada SMK Negeri 1 Bandar Lampung - Rini Nurlistiani; Ochi Marshella Febriani; Indera; Reni Wardati (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
The system at SMK Negeri 1 Bandar Lampung for collecting internship reports, journals, e-books and scientific works is still not efficient and effective because they still collect reports manually and there is no system for disseminating e-books or journals. To improve the development of information technology at SMK Negeri 1 Bandar Lampung, a system is needed that can carry out this process, namely a website-based repository system. The repository system development methodology uses the Extreme Programming method, because the Extreme Programming method is more structured and easier to develop the system. The results of this system are implemented on a website, this system can upload internship reports, journals or e-books, and this system can carry out online guidance processes between student-teachers, student-externals and teacher-externals online on the website.